PENGARUH OPINI GOING CONCERN, PERGANTIAN MANAJEMEN, KESULITAN KEUANGAN, DAN REPUTASI AUDITOR PADA AUDITOR SWITCHING - Yudha, Cok Krisna; Rasmini, Ni Ketut; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study aims to analyze the effect of goingconcern opinion s , managementchange, financial distress and auditor reputation in the auditor switching as well as to examine differences in the effect of goingconcern opinion s , managementchange, financial di stress and auditor reputation on auditors switching between large, medium and small enterprises . The research data were collected from open manufacturing enterprises (Tbk) listed on the ISE. The n umber of observations was 368 observations from 2013 - 2015.The method of analysis used logistic regression test and test of regression coefficient difference. The results of the study indicate d that there was an effect of financial di stress and the auditor reputation on the auditor switching. However, going-concern opinions and managementchange would not affect auditorsswitchin g . The results also conclude d that there were differences in the effect of going-concern opinion s , managementchange, financial dis tress and auditors reputation at auditors switching between large and small enterprises .